Risk factors for outbreaks of COVID‐19 in care homes following hospital discharge: A national cohort analysis. Issue 3 (6th February 2021) - Emmerson, Chris; Adamson, James P.; Turner, Drew; Gravenor, Mike B.; Salmon, Jane; Cottrell, Simon; Middleton, Victoria; Thomas, Buffy; Mason, Brendan W.; Williams, Chris J.
Abstract: Background: The population of adult residential care homes has been shown to have high morbidity and mortality in relation to COVID‐19. Methods: We examined 3115 hospital discharges to a national cohort of 1068 adult care homes and subsequent outbreaks of COVID‐19 occurring between 22 February and 27 June 2020. A Cox proportional hazards regression model was used to assess the impact of time‐dependent exposure to hospital discharge on incidence of the first known outbreak, over a window of 7‐21 days after discharge, and adjusted for care home characteristics, including size and type of provision. Results: A total of 330 homes experienced an outbreak, and 544 homes received a discharge over the study period. Exposure to hospital discharge was not associated with a significant increase in the risk of a new outbreak (hazard ratio 1.15, 95% CI 0.89, 1.47, P = .29) after adjusting for care home characteristics. Care home size was the most significant predictor. Hazard ratios (95% CI) in comparison with homes of <10 residents were as follows: 3.40 (1.99, 5.80) for 10‐24 residents; 8.25 (4.93, 13.81) for 25‐49 residents; and 17.35 (9.65, 31.19) for 50+ residents. When stratified for care home size, the outbreak rates were similar for periods when homes were exposed to a hospital discharge, in comparison with periods when homes were unexposed. Conclusion: Our analyses showed that large homes were at considerably greater risk of outbreaks throughout the epidemic, and after adjusting for care home size, a discharge from hospital was not associated with a significant increase in risk.